FLUid management and InDividualized resuscitation in Sepsis (FLUIDS)—A Study protocol for a single-centre, open-label, randomized clinical trial - Sanne Ter Horst; Ewoud Ter Avest; Jildou van Everdink; Matijs van Meurs; Tycho J. Olgers; Jaap Jan Vos; Kevin Damman; Jan C. ter Maaten; Hjalmar R. Bouma (PLoS ONE, 2025)
Introduction Early septic shock results from complex hemodynamic disturbances, including vasodilation, capillary leakage, and hypovolemia, requiring timely resuscitation to prevent organ failure. Initial fluid administration in the emergency department (ED) varies widely, influenced by clinician experience, patient comorbidities, and infection source. Fluid therapy is frequently not tailored to individual patient responsiveness and tolerance, highlighting the importance of personalized resuscitation strategies. Objective This study evaluates the effectiveness of a personalized hemodynamic resuscitation strategy during the initial management of sepsis in the ED, using continuous non-invasive stroke volume index (SVI) measurements to guide intravenous (IV) fluid therapy and early vasopressor initiation. Method This single-centre, open-label, randomized clinical trial at the Emergency Department of the University Medical Centre Groningen, the Netherlands, will enroll 188 adults with suspected sepsis requiring hemodynamic resuscitation, defined by a mean arterial pressure (MAP) <70 mmHg, systolic blood pressure (SBP) <90 mmHg, shock index >0.9, or lactate concentration >4.0 mmol/L. Deferred consent will be obtained within 30 days of ED presentation. Patients will be randomized to the intervention group, in which fluids and vasopressors will be guided by changes in SVI (ΔSVI) after IV fluid administration, or to the control group, where fluids and vasopressors will be administered at the discretion of the treating physician during the initial 3-hour resuscitation phase. The primary endpoint is the volume of IV fluids administered within the first three hours after enrollment. Secondary endpoints include cumulative fluid balance, timing and dose of vasopressors, incidence of organ failure, hospital length of stay, mortality and fluid-related adverse events, including venous congestion assessed by point-of-care ultrasound. Expected results We anticipate that SVI-guided resuscitation will reduce IV fluid volume compared to standard care. This personalized approach, tailoring fluid and vasopressor administration to the individual’s hemodynamic needs, has the potential to improve outcomes for patients with sepsis. Trial registration ClinicalTrials.gov NCT07009665